First Report of Ganoderma ryvardenii causing Basal Stem Rot (BSR) disease on oil palm (Elaeis guineensis Jacq.) in Ghana [version 2; peer review: 1 approved, 2 approved with reservations] - Frank K. Ackah; Grace C. van der Puije; Emmanuellah Lekete-Lawson; Enoch A. Osekre (F1000Research)
Backgrounds Oil palm (Elaeis guineensis Jacq.), is the most significant and highest-yielding crop among oil-producing crops worldwide. In 2020/2022, Basal stem rot (BSR) disease was observed in six oil palm growing Districts in Ghana. Methods Field study and laboratory analysis were conducted. A random sampling technique was used to select five plantation blocks from each District. Single-point disease assessments were done using Standard Operating Procedure (SOP) with a severity scale of 0-4. Molecular assays were performed on each sample using nucleic acid as a template. ITS and GanET sequence analysis were performed along with the formation of a phylogenetic tree using the FASTA algorithm with the Fungus database from EBI and NCBI GenBank. Koch’s postulate was followed to confirm the disease. Results The disease incidence was 11.3 % with the highest severity score of 4. Basal Stem Rot (BSR) is characterised by progressive stem decay coupled with the formation of large, perennial, woody basidiocarps. The average measurement of 2-65 cm in diameter on infected palms. Culture colonies were white, striated, undulating, woolly-cottony, and creamish pigment on the reverse, depicting attributes of Ganoderma fungus. Molecular confirmation was done by combining the ITS sequence of top matches of >97% to members of the genus Ganoderma, >98% and 99.3% identity to three sequences of Ganoderma sp. (HM138671; HM138670 and HM138672) generated from strains assigned to Ganoderma ryvardenii and compared with 132 published sequences of Ganoderma isolates. Conclusion This study presents the first report of Ganoderma ryvardenii causing BSR disease on oil palm in Ghana, potentially the first in West Africa, and second in Africa. Notably, the pathogen was previously first reported to cause similar disease on oil palm in Cameroon, highlighting its emerging threat to oil palm production in the Sub-Saharan African region.